Dose Assessment for Technologically Enhanced Naturally Occurring Radioactive Materials Disposal in Landfills. Issue 3 (6th September 2021) - Caffrey, Emily A.; Rood, Arthur S.; Grogan, Helen A.; Till, John E.; Herman, Kurt
Abstract: Technologically enhanced naturally occurring radioactive material (TENORM) is gaining notoriety in the public sector, as the oil and gas industry looks for disposal locations for its slightly radioactive waste streams. Due in part to both the lack of federal regulations on the disposal of TENORM and the lack of permitted landfills that are designated for TENORM waste, occasionally it ends up being unknowingly placed in municipal landfills. It was alleged that a municipal landfill in Kentucky accepted 1.05 × 106 kg of TENORM over approximately 8 mo starting in July 2015. This matter is still in litigation, and many facts, including whether the material in question actually constituted TENORM, are still in dispute. The authors had no means available to independently verify the actual composition of the material. Therefore, for purposes of this article only, we assume that the material in question did constitute TENORM. This qualification allows us to evaluate potential doses while respecting the litigation process. Doses from the disposals and for two remediation alternatives, (1) closure-in-place and monitoring and (2) excavation and redisposition of waste, were evaluated, taking into consideration the landfill construction, local geology and hydrology, meteorology, background radiation, population distribution, and current and future land uses. This study outlines appropriate methods for calculating doses to potential receptors for a variety of exposure pathways that are broadly applicable to municipal or chemical/hazardous waste landfills. As this study demonstrates, doses to landfill workers and members of the public are low, both during the disposal and for the remediation alternatives evaluated, and well below regulatory limits. Removal of the materials does not reduce present day doses, and it presents other risks that outweigh any benefit from the long-term dose reduction.